2008
DOI: 10.1016/j.molcel.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Unique Contacts Direct High-Priority Recognition of the Tetrameric Mu Transposase-DNA Complex by the AAA+ Unfoldase ClpX

Abstract: Clp/Hsp100 ATPases remodel and disassemble multiprotein complexes, yet little is known about how they preferentially recognize these complexes rather than their constituent subunits. We explore how substrate multimerization modulates recognition by the ClpX unfoldase using a natural substrate, MuA transposase. MuA is initially monomeric but forms a stable tetramer when bound to transposon DNA. Destabilizing this tetramer by ClpX promotes an essential transition in the phage Mu recombination pathway. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…In this manner, the discriminator site may be analogous to the "enhancement tags" found in some other AAA+ unfoldase substrates. These short peptide signals serve to enhance recognition in the overall enzyme-substrate complexes and focus unfoldase action to the proper conformation or stage of the substrate's lifecycle (24)(25)(26). This hypothesis is also consistent with previous observations that Lon contains more than one site for substrate recognition (10,27).…”
Section: Discussionsupporting
confidence: 89%
“…In this manner, the discriminator site may be analogous to the "enhancement tags" found in some other AAA+ unfoldase substrates. These short peptide signals serve to enhance recognition in the overall enzyme-substrate complexes and focus unfoldase action to the proper conformation or stage of the substrate's lifecycle (24)(25)(26). This hypothesis is also consistent with previous observations that Lon contains more than one site for substrate recognition (10,27).…”
Section: Discussionsupporting
confidence: 89%
“…4). Previous studies showed that ClpXP disassembles the wild-type STC1 with an apparent K M of ∼1.0 μM and an apparent V max of ∼3.1∕ min (21). We found that ClpXP disassembled the double right-end transpososome with an apparent K M of ∼1.1 μM and an apparent V max of ∼3.5∕ min (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Because DHFRII is a tetramer, it is likely that a O tag from one subunit tethers the substrate to the N-domain of ClpX, allowing the O tag from a second subunit to be engaged by ClpX for degradation. Recent studies indicate that ClpX disassembly of the tetrameric MuA transposase also involves recognition of multiple classes of sequence elements (29).…”
Section: Discussionmentioning
confidence: 99%